THE ORTHODOX ALTAI IN CONTEMPORARY RUSSIAN CULTURE - V. V. Pechatnov (Концепт: философия, религия, культура, 2018)
The article traces the history of Russian Orthodoxy in Altai from its beginning in early XVIII c. down to the present, showing its impact on the surrounding culture. The author demonstrates the decisive role of the Altai Orthodox Mission not only in the propagation of the Orthodox faith among the local population, but in its cultural transformation. In particular, Russian missionaries in Altai, especially the canonized saints archimandrite Makarii (Glukharev, 1793-1847) and metropolitan Makarii (Nevskii, 1835-1926), gave the Altai people the alphabet, writing system, and literary language, taught them to build houses and settlements and to maintain a settled economy. The article also shows that pre-revolutionary missionary monasteries in Altai contributed much to the region’s cultural and social life.The focus of the article is on the Orthodox Altai today, particularly on the revival of Orthodoxy in the Chemal village in the mountain part of Altai. In the 1990s-2000s Moscow photographer V.N. Pavlov (1937-2011) restored on the so-called “Altai Patmos” – a small island on the Katun river – the church which was there in the early XX c., and built a suspension bridge to the island. Then on the shore facing the island a female monastic settlement was founded, and later a Bishop’s house with a church and museum were added. This place has become a center of pilgrimage not only for local residents, but also for guests from other parts of Russia and abroad.The article concludes with an overview of the contemporary centers of Orthodox pilgrimage in Altai with an indication of their cultural significance.